Effect of feeding frequency on growth, feed utilisation and cannibalism in climbing perch Anabas testudineus (Bloch 1792) fry - Dash, Lipsha; Kumar, Rajesh; Mohanta, K. N.; Mohanty, U. L.; R. Pillai, Bindu; Sundaray, J. K. (Indian Journal of Fisheries, 2019)
A 35 days experiment was conducted to study the effect of different feeding frequencies on growth and feed utilisation in climbing perch Anabas testudineus (Bloch 1792) fry. Four different feeding frequencies in triplicate viz., 2 (T1), 3 (T2), 4 (T3) and 5 (T4) times a day were evaluated. Fry (144 nos.) of climbing perch were randomly distributed in 12 glass aquaria (50 l) containing 25 l of filtered and well aerated freshwater. Formulated pellet feed was prepared and fed @ 6% body weight to all the experimental groups at different feeding frequencies as mentioned above. At the end of the experiment, fishes were sampled to determine weight gain percentage (WG %), specific growth rate (SGR), food conversion ratio (FCR), protein efficiency ratio (PER), survival percentage (%) and partial cannibalism rate (%). Results revealed that the WG% (112.80±2.25), PER (1.65±0.03) and SGR (2.15±0.03) were significantly higher (p<0.05) in T3 group. FCR (1.55±0.03) was lowest in T3 group. Partial cannibalism rate (%) was significantly higher (p<0.05) in the treatment group T1 (6.33±0.88) whereas the survival rate (%) was lowest in T1 (91.66±4.81). The results therefore, indicated that feeding frequency of 4 times a day (T3) could be the ideal feeding frequency for better growth and feed utilisation during fry rearing of climbing perch.